Policies, education, research and environmental broadcast networks - Lovera Dávila, Daniel Florencio (2016)
1947/5000       The National University of San Marcos has incorporated in its strategic plan the environmental commitment, in the mission and vision mention is made of the commitment of the students to the environment. Accreditation encourages us to take into account the environmental dimension. The Professional Schools also consider the environmental theme in their study plan; the lines of research consider the environmental and climate change variables; while, the Postgraduate Units have their diplomas, master's degrees and doctorates in solving environmental problems. The incorporation of the environmental theme is growing and has great interest on the part of the university community. The climate change and risk management office coordinates and fosters the training and formation of human capital, both for students and teachers in environmental issues. In this global environmental framework, the Research Institute of the Faculty of Geological, Mining, Metallurgical and Geographical Engineering-FIGMMG; In conjunction with the Biosfera Foundation (Argentina), initiatives and visions were joined to develop the regional forum called Meeting of Environmental Managers of provinces and states of Latin America and the Caribbean permanently held in 2014, 2015, 2016, and subsequent years. These meetings took place in the days prior to the World Summit on Climate Change (COP), where local, regional and global environmental problems were analyzed. Under these international policies and standards, university professors and research groups have been developing a variety of projects to adapt to current climate changes, as well as devising strategies to mitigate such variations at the national and international levels. The results of these investigations will be disseminated through publications in the magazine of the FIGMMG Research Institute.